New suns : original speculative fiction by people of color - Shawl, Nisi; Buckell, Tobias S.; Alcalá, Kathleen, 1954-; Kang, Minsoo; Barnes, Steven, 1952-; Onwualu, Chinelo; Jennings, Alex; Yáñez, Alberto; Goh, Jaymee; Yu, E. Lily; Lowachee, Karin; Moreno-Garcia, Silvia; et al. (Solaris, an imprint of Rebellion Publishing Ltd, 2019)
"'There's nothing new under the sun, but there are new suns,' proclaimed Octavia E. Butler. New Suns: Original Speculative Fiction by People of Color showcases emerging and seasoned writers of many races telling stories filled with shocking delights, powerful visions of the familiar made strange. Between this book's covers burn tales of science fiction, fantasy, horror, and their indefinable overlappings. These are authors aware of our many possible pasts and futures, authors freed of stereotypes and clichés, ready to dazzle you with their daring genius. Unexpected brilliance shines forth from every page."--Back cover.